2017
DOI: 10.1016/j.acra.2017.05.007
|View full text |Cite
|
Sign up to set email alerts
|

The Reproducibility of Changes in Diagnostic Figures of Merit Across Laboratory and Clinical Imaging Reader Studies

Abstract: Rationale and Objectives In this paper we examine which comparisons of reading performance between diagnostic imaging systems made in controlled retrospective laboratory studies may be representative of what we observe in later clinical studies. The change in a meaningful diagnostic figure of merit between two diagnostic modalities should be qualitatively or quantitatively comparable across all kinds of studies. Materials and Methods In this meta-study we examine the reproducibility of relative sensitivity, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…In an outside meta-analysis of 20 studies, ROC-AUC was shown to be an efficient way to simultaneously capture the performance of a device on cancer and non-cancer cases in MRMC studies across laboratories and a better method for predicting performance in clinical studies than cancer and noncancer recall rates (36). In line with this, it is the preferred accuracy statistical metric for comparisons of the U.S. Food and Drug Administration (37).…”
Section: Discussionmentioning
confidence: 92%
“…In an outside meta-analysis of 20 studies, ROC-AUC was shown to be an efficient way to simultaneously capture the performance of a device on cancer and non-cancer cases in MRMC studies across laboratories and a better method for predicting performance in clinical studies than cancer and noncancer recall rates (36). In line with this, it is the preferred accuracy statistical metric for comparisons of the U.S. Food and Drug Administration (37).…”
Section: Discussionmentioning
confidence: 92%
“…153,154 A common approach for assessing clinical performance is through a controlled reader study (either retrospective or prospective), directly comparing the performance of a human reader without and with output from the CAD-AI system. 155,156 A disadvantage of this approach is that the estimated performances are unlikely to match those in the true clinical setting because of differences in the cases, physicians, and reading process. It is important to realize that both the population of patients undergoing the examination (cases) and the population of physicians interpreting the data (readers) are sources of substantial variability in clinical reader studies.…”
Section: Clinical Reader Performance Assessmentmentioning
confidence: 99%
“…A clinical reader performance assessment is used to estimate the clinical impact of a CAD‐AI algorithm 153,154 . A common approach for assessing clinical performance is through a controlled reader study (either retrospective or prospective), directly comparing the performance of a human reader without and with output from the CAD‐AI system 155,156 . A disadvantage of this approach is that the estimated performances are unlikely to match those in the true clinical setting because of differences in the cases, physicians, and reading process.…”
Section: Performance Assessmentmentioning
confidence: 99%